Protective role of sodium silicate against water stress in Lycopersicon esculentum mill. - CHANCHAL MALHOTRA; RITI THAPAR KAPOOR; DEEPAK GANJEWALA (International Journal of Pharma and Bio Sciences, 2016)
The change in climatic conditions are adversely affecting our environment. Drought is one of the major constraints limiting crop production worldwide. In the present study, impact of sodium silicate on the growth parameters of tomato (Lycopersicon esculentum Mill. variety Pusa 120) was analyzed at vegetative, flowering and fruiting stages.The significant increase in morphological parameters of tomato plants were observed in T1 treatment (5g sodium silicate) in comparison to T2 treatment (7g sodium silicate) and control.The results of the present investigation clearly indicates that sodium silicate acts as a plant growth promoter and it can be used in drought prone areas for the protection of crops against water stress.